Edge Computing Research – A Review (Journal of Information Technology and Digital World, 2023)
As the world is moving towards digitalization and automation, a large amount of data is being generated from various domains. In most of the data-driven applications, the large-scale data must be quickly processed in order to assist the state-of-the-art technologies like Internet of Everything (IoE). To increase the response speed and bandwidth load, the existing cloud computing models are not sufficient. This has led to the development of edge computing. The edge computing paradigm extends its support to the diversified requirements of today’s digital society. In contrast to cloud computing, edge computing remains more closer to both the data source and end-user remaining at the edge of the network as a small-scale and local data processing unit. This research study reviews the concept of edge computing and how it varies from cloud computing. First, the article describes the purpose and necessity for edge computing, as well as the differences between edge and cloud computing. Then, highlights the advantages of potential edge computing architectures. Finally, a summary of the new edge computing initiatives is provided.
Keywords: Networking; Cloud Computing; Edge Computing; Internet of Things; Data Analysis